BIM Information Classification and Codification for manufacturing Heritage Buildings. Issue 1 (1st June 2022) - Lu, Shizhong; Yu, Zhimin; Zhou, Zejia; Wei, Longming; Luo, Zhihua
Abstract: Heritage buildings have gained great popularity lately due to the attraction of the unique culture embedded in the heritage building elements and the incentive policies of the government to publicize traditional culture. manufacturing construction has been adopted in the construction industry due to many advantages over traditional on-site construction. However, the construction industry is still dominated by traditional on-site construction methods, and existing research in manufacturing construction mainly focuses on modern architecture styles. There is little discussion on the application of manufacturing construction to heritage buildings, especially on the integration of digital technology. This article proposes a BIM information classification method and the key information codification system to support the lifecycle management of manufacturing heritage buildings with BIM as the basic digital technology carrier, and two cases are used to verify its effectiveness.